Group-Based Trajectory of Body Shape From Ages 5 to 55 Years and Cardiometabolic Disease Risk in 2 US Cohorts - Zheng, Yan (Am J Epidemiol, 2017)
The association of adiposity across the life span with cardiometabolic risk is not completely delineated. We used a group-based modeling approach to identify distinct trajectories of body shape from ages 5 years to 55 years among 84,792 women from the Nurses’ Health Study (1976–2010) and 37,706 men from the Health Professionals Follow-up Study (1986–2010) and assessed the associations between these trajectories and incidence of type 2 diabetes and cardiovascular disease (CVD) during a 17-year follow-up period. Compared with those who maintained leanness throughout the life span (“lean-stable” trajectory), participants who maintained a medium body shape (“medium-stable” trajectory) had somewhat increased risk. Those who started lean but had a moderate or marked increase in adiposity (“lean-moderate increase” and “lean-marked increase” trajectories) had even higher risk (e.g., for a “lean-marked increase” trajectory, the hazard ratio for diabetes was 8.11 (95% confidence interval (95% CI): 7.10, 9.27) in women and 2.36 (95% CI: 2.04, 2.74) in men; for CVD, it was 1.38 (95% CI: 1.25, 1.52) in women and 1.28 (95% CI: 1.16, 1.41) in men). Participants who started heavy and became heavier (a “heavy-increase” trajectory) had substantially elevated risk (for diabetes, the hazard ratio was 7.34 (95% CI: 6.40, 8.42) in women and 2.80 (95% CI: 2.37, 3.31) in men; for CVD, it was 1.55 (95% CI: 1.40, 1.71) in women and 1.35 (95% CI: 1.20, 1.53) in men). Our data showed that trajectories of body shape from ages 5 to 55 years were associated with subsequent risk of developing type 2 diabetes and CVD.